Do stock price bubbles influence corporate investment? - Simon Gilchrist; Charles P. Himmelberg; Gur Huberman (Federal Reserve Bank of New York, 2004)
Building on recent developments in behavioral asset pricing, we develop a model in which an increase in the dispersion of investor beliefs under short-selling constraints predicts a bubble, or a rise in a stock's price above its fundamental value. Our model predicts that managers respond to bubbles by issuing new equity and increasing capital expenditures. We test these predictions, as well as others, using the variance of analysts' earnings forecasts - a proxy for the dispersion of investor beliefs - to identify the bubble component in Tobin's Q. When comparing firms traded on the New York Stock Exchange with those traded on NASDAQ, we find that our model successfully captures key features of the technology boom of the 1990s. We obtain further evidence supporting our model by using a panel-data VAR framework. We find that orthogonalized shocks to dispersion have positive and statistically significant effects on Tobin's Q, net equity issuance, and real investment - results that are consistent with the model's predictions.
Keywords: E22; G31; G32; D92; 330; investment; stock market; bubble; dispersion; Börsenkurs; Bubbles; Investition; Tobin's Q; USA